A comparison of data quality and practicality of online versus postal questionnaires in a sample of testicular cancer survivors. Issue 1 (26th September 2011) - Smith, Allan 'Ben'; King, Madeleine; Butow, Phyllis; Olver, Ian
Abstract Objective We aimed to compare data quality from online and postal questionnaires and to evaluate the practicality of these different questionnaire modes in a cancer sample. Methods Participants in a study investigating the psychosocial sequelae of testicular cancer could choose to complete a postal or online version of the study questionnaire. Data quality was evaluated by assessing sources of nonobservational errors such as participant nonresponse, item nonresponse and sampling bias. Time taken and number of reminders required for questionnaire return were used as indicators of practicality. Results Participant nonresponse was significantly higher among participants who chose the postal questionnaire. The proportion of questionnaires with missing items and the mean number of missing items did not differ significantly by mode. A significantly larger proportion of tertiary‐educated participants and managers/professionals completed the online questionnaire. There were no significant differences in age, relationship status, employment status, country of birth or language spoken by completion mode. Compared with postal questionnaires, online questionnaires were returned significantly more quickly and required significantly fewer reminders. Conclusions These results demonstrate that online questionnaire completion can be offered in a cancer sample without compromising data quality. In fact, data quality from online questionnaires may be superior due to lower rates of participant nonresponse. Investigators should be aware of potential sampling bias created by more highly educated participants and managers/professionals choosing to complete online questionnaires. Besides this issue, online questionnaires offer an efficient method for collecting high‐quality data, with faster return and fewer reminders. Copyright © 2011 John Wiley & Sons, Ltd.